2019
DOI: 10.3390/polym11071156
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Thermal Conductivity in Epoxy Composites: Effect of Boron Nitride Particle Size and Matrix-Filler Interface

Abstract: For the thermal management of high watt density circuit layers, it is common to use a filled epoxy system to provide an electrically insulating but thermally conducting bond to a metal substrate. An epoxy-thiol system filled with boron nitride (BN), in the form of 2, 30 and 180 µm platelets, has been investigated with a view to achieving enhanced thermal conductivity. The effect of BN content on the cure reaction kinetics has been studied by differential scanning calorimetry and the thermal conductivity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 23 publications
2
75
0
Order By: Relevance
“…Most noticeably, the shift is much greater for the smallest (2 µm) particles, with rather similar shifts for the other particles. This effect, which has been reported in earlier work and occurs also for epoxy-thiol composites filled with aluminium nitride particles, appears to be peculiar to epoxy systems cross-linked with thiol [21,29,30].…”
Section: Differential Scanning Calorimetrysupporting
confidence: 80%
See 1 more Smart Citation
“…Most noticeably, the shift is much greater for the smallest (2 µm) particles, with rather similar shifts for the other particles. This effect, which has been reported in earlier work and occurs also for epoxy-thiol composites filled with aluminium nitride particles, appears to be peculiar to epoxy systems cross-linked with thiol [21,29,30].…”
Section: Differential Scanning Calorimetrysupporting
confidence: 80%
“…In addition, although the BN particles are inert and hence would not a priori be expected to influence the chemical cure reaction, we have observed earlier that, for this epoxy-thiol system, there are some systematic effects of BN content on the reaction kinetics [21,29,30]. These effects were correlated to some extent with the thermal conductivity measurements, suggesting that the matrix-filler interface, so crucial to the thermal conductivity and dependent on SSA and filler particle shape and/or size, plays an important role also in the cure kinetics.…”
Section: Introductionmentioning
confidence: 88%
“…This is also illustrated in Figure 8, for the case of the BN particles not treated with silane; the same trend was reported for the silane-treated particles, for which higher thermal conductivities were observed, but for clarity these are not included in Figure 8. show a trend of increasing thermal conductivity as the BN particle size decreases, which contrasts with the usual observed effect of particle size [64,65]. This is also illustrated in Figure 8, for the case of the BN particles not treated with silane; the same trend was reported for the silane-treated particles, for which higher thermal conductivities were observed, but for clarity these are not included in Figure 8.…”
Section: Effect Of Bn Contentmentioning
confidence: 71%
“…These authors suggested that the Lewis acid-base interaction between the sulphur in the thiol and the boron in the filler leads to an improved matrix-filler interface, which was the reason for the enhanced thermal conductivity. In support of this hypothesis, they reported that the same epoxy-BN system cured with a diamine does not give such high thermal conductivities, for example only 1.7 W/mK at 53 wt.% BN [65]. They also noted that the cure kinetics of the epoxy-thiol system and the epoxy-diamine system are quite different in their dependence on the BN content, as discussed in Section 2, and consider this to be further evidence of the favourable matrix-filler interaction in the epoxy-thiol-BN composite system.…”
Section: Effect Of Surface Treatments and Coupling Agentsmentioning
confidence: 92%
“…While this work focuses its attention on 12 µm diameter W particles, it is well known that size parameters can affect mixture properties. For a fixed volume fraction of filler particles, the thermal conductivity decreases and the viscosity increases as the particle diameter decreases . Although larger particle diameters should increase thermal conductivity, we note that paste‐like TIMs are quite thin and this places an upper limit on particle diameter (see Section S7 in the Supporting Information).…”
mentioning
confidence: 90%